207k views
0 votes
What are the steps you should follow to solve this equation. I don't need the solution, just the steps. 4x + 3 - 2x = 5x - 2 - x

2 Answers

3 votes

Answer:

x = 5/2

Explanation:

4x + 3 - 2x = 5x - 2- x

Re-writing the eqn, we get,

4x - 2x + 3 = 5x - x - 2

2x + 3 = 4x - 2

3 + 2 = 4x - 2x

5 = 2x

∴ x = 5/2

User Peter Nied
by
5.5k points
4 votes
first simplify so. 2x+3=4x-2. then subtract 4x from both sides. so u get -2x+3=-2. then subtract 3 from both sides so -2x=-5. then finally divide both sides by -2 so u get x=5/2
User ShibbyUK
by
5.9k points